o-Carboranylalkoxy-1,3,5-Triazine Derivatives: Synthesis, Characterization, X-ray Structural Studies, and Biological Activity - Guo Fan Jin; Hyun Seung Ban; Hiroyuki Nakamura; Jong-Dae Lee (Molecules, 2018)
Morpholine- and bis(2-methoxyethyl)amine-substituted 1,3,5-triazine derivatives containing an alkoxy-o-carborane in the 6-position of the triazine ring were successfully synthesized. The molecular structures of the methoxy- and ethoxy-o-carboranyl-1,3,5-triazines were established by X-ray crystallography. In vitro studies showed that the methylene bridged morpholine- and bis(2-methoxyethyl)amine-substituted o-carboranyl-1,3,5-triazines accumulated to high levels in B16 melanoma cells and exhibited higher cytotoxicity than p-boronophenylalanine.